Genome-wide association studies identified OsTMF as a gene regulating rice seed germination under salt stress - Liu, Lifeng; Ma, Yanling; Zhao, Heng; Guo, Lin; Guo, Yan; Liu, Chun-Ming (Frontiers in Plant Science, 2024)
Salt tolerance during seed germination is an important trait for direct seeding and lowcost rice production, nevertheless, how seed germination under salt stress is regulated genetically is not clear. In this study, genome-wide association studies were performed to decipher the genetic basis of seed germination under salt stress using 541 rice varieties collected worldwide, and three quantitative trait loci (QTLs) were identified including qGRG3-1 on chromosome 3, and qGRG3-2 on chromosome 5, and qGRG4 on chromosome 4. Assessment of candidate genes in these loci for their responses to salt stress identified a TATA modulatory factor (OsTMF) in qGRG3-2. The expression of OsTMF was up-regulated in both roots and shoots after exposure to salt stress, and seeds produced in OsTMF knockout mutants exhibited delayed germination under salt stress. Haplotype analysis showed that rice varieties carrying OsTMF-Hap2 displayed elevated salt tolerance during seed germination. These results provide important knowledge and resources to improve rice seed germination under salt stress in the future.